Empowering Overseas Indonesian Citizens: Voter Education Training for First-Time Voters - Gunawan, Yordan; Genovés, Manuel Beltrán (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
This discussion focused on the participation of first-time Indonesian voters abroad, particularly in Spain, in the 2024 general election. These voters hold great potential to shape the political and policy direction of their home country but face challenges such as limited access to information and a lack of understanding of domestic politics. To address these issues, a community service program was implemented to provide targeted political education, leverage technology and social media, and foster collaboration with local Indonesian communities. The program's methods included a series of online workshops, informative social media campaigns, and partnerships with local organizations to enhance political literacy. The results of the program demonstrated a significant improvement in voter knowledge and engagement, with a marked increase in voter registration and political awareness among first-time voters compared to pre-program levels. This effort aims to ensure that the voices of all Indonesian citizens, regardless of location, are heard and contribute to the democratic process, ultimately strengthening Indonesia's democracy.